Fixed Asset Management: The Role of Regional Asset Information Systems in the Utilization of Unused Assets in the Local Government of Bengkalis Regency - Sri Wahyuni, Endang; Nur Rahmani (E-Jurnal Akuntansi, 2025)
Fixed asset management is an essential part of regional financial governance. However, many regional assets remain unused (idle assets), leading to inefficiencies and additional maintenance costs. This study aims to analyze the role of the Regional Management Information System for Regional Property (SIMDA BMD) in optimizing the utilization of unused fixed assets in the Bengkalis Regency Government. A qualitative approach was applied with data collected through documentation, interviews, and observations involving the Head of Asset Subdivision, accounting staff, and asset managers. The findings reveal that SIMDA BMD contributes to improving the accuracy of asset recording and transparency of information but has not been effective in identifying idle assets. The local government is committed to migrating to the e-BMD system to enable real-time monitoring and utilization of idle assets. These findings are expected to contribute to developing more effective, accountable, and value-oriented regional asset management practices.